Systems Biology Strategy Reveals PKCδ is Key for Sensitizing TRAIL-Resistant Human Fibrosarcoma - Hayashi, Kentaro; Tabata, Sho; Piras, Vincent; Tomita, Masaru; Selvarajoo, Kumar (Frontiers in Immunology, 2015)
Cancer cells are highly variable and resistant to therapeutic intervention. Recently, the use of the tumor necrosis factor related apoptosis-inducing ligand (TRAIL) induced treatment is gaining momentum, due to TRAIL’s ability to specifically target cancers with limited effect on normal cells. However, several malignant cancer types still remain non-sensitive to TRAIL. Previously, we developed a dynamic computational model, based on perturbation-response approach, and predicted protein kinase C (PKC) as the most effective target, with over 95% capacity to kill human fibrosarcoma (HT1080) in TRAIL stimulation (Piras, V. et al. 2011, Scientific Reports). Here, to validate the model prediction, which has significant implications for cancer treatment, we conducted experiments on two TRAIL-resistant cancer cell lines (HT1080 and HT29). Using PKC inhibitor Bisindolylmaleimide I, we first demonstrate, as predicted by our previous model, cell viability is significantly impaired with over 95% death of both cancer types. Next, to identify crucial PKC isoform from 10 known members, we analyzed their mRNA expressions in HT1080 cells and shortlisted 4 isoforms for siRNA knock-down (KD) experiments. From these KDs, PKC-delta produced the most cancer cell death in conjunction with TRAIL. Overall, systems biology approach, combining model prediction with experimental validation, holds promise for TRAIL-based cancer therapy.